Consumptive Culture in BTS Fandom (ARMY) in D.I.Yogyakarta - Vivian Vebryanti; Taufiqur Rahman (Jogjakarta Communication Conference (JCC), 2023)
This study aims to analyze about the consumptive culture that were found in the online community of ARMY Yogyakarta which is part of the BTS Jogja community on Instagram. This research uses a descriptive qualitative research method with a type of research method in the form of virtual ethnography, with a data collection method consisting of virtual observation from bts_jogja Instagram account, interviews with several respondents online, and documentation. The result of this study shows that consumptive culture was tied with fan cultures, and as a fan base, bts_jogja Instagram accounts has an influence on developing consumptive culture towards ARMY Yogyakarta community that caused by their fan projects, their Instagram posts, and their Instagram story. Especially if they had a collaboration with mini K-pop outlets to sell merchandise.